2015
DOI: 10.1364/boe.7.000057
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of cutaneous melanoma from surrounding skin using laser-induced breakdown spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS) has the potential to be used as a surgical tool for simultaneous tissue ablation and elemental analysis of the ablated tissue. LIBS may be used to distinguish melanoma lesions from the surrounding dermis based on the quantitative difference of elements within melanoma lesions. Here, we measured the elements in homogenized pellets and real tissues from excised skin samples of melanoma-implanted mice. In addition, statistical analysis of LIBS spectra using principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 21 publications
1
42
1
2
Order By: Relevance
“…11 For the case of melanoma, we reported in our recent study that melanoma and surrounding dermis could be distinguished by LIBS with high sensitivity using Mg and Ca emission peaks as the biomarkers. 12 Although it was an early stage of research yet, this study confirmed that LIBS can be an effective method to identify melanoma from normal tissue.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…11 For the case of melanoma, we reported in our recent study that melanoma and surrounding dermis could be distinguished by LIBS with high sensitivity using Mg and Ca emission peaks as the biomarkers. 12 Although it was an early stage of research yet, this study confirmed that LIBS can be an effective method to identify melanoma from normal tissue.…”
Section: Introductionsupporting
confidence: 61%
“…On the contrary, the difference in pigment density between melanoma and dermis is considered to have little influence in the signal intensity change, because, in our previous study for LIBS analyses of melanoma with pellet and excised tissue samples, Mg intensity was found to be also higher in melanoma even after the absorption property difference between pigmented and nonpigmented regions was compensated by normalization. 12…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations